The Role of Media in implanting Education Values in Iraqi Child - Hoisin, Thanaa Mutalib; Al-Salihi, Noah Izzidden (Al-Adab Journal, 2021)
Our current research aims to know the role of the media in implanting the educational values of the Iraqi child. This is after the media; the way the child communicates with the surrounding community. They help him to interact properly, create creativity, and improve learning. Social media networks work to attract children as they are new and unconventional networks. Because it encourages the shy and lonely to express themselves easily and easily. In order to reach to verify the objectives and hypotheses of the research. The researchers identified a set of educational values, totaling (14) educational values, which the media work to instill in children according to what has been mentioned in the previous literature. Then they built an exploratory questionnaire consisting of (34) questions, which were distributed to a sample of children aged between (11-16) years. The research sample consisted of (600) children, by (300) children of males, and (300) children of females, and after extracting validity and reliability factors for the research questionnaire. And then applying its items to the sample, the children’s answers were analyzed to confirm the role of the media in implanting their educational values, and the results have shown that the media have a